Tibial eminence fracture with midsubstance anterior cruciate ligament tear in a 10-year-old boy: A case report - Yamauchi, Shohei (Int J Surg Case Rep, 2020)
INTRODUCTION: There are few reports about tibial eminence fractures with a concomitant midsubstance ACL tear in children. In this report, we present a case of a tibial eminence fracture with an ACL midsubstance tear in a 10-year-old boy. PRESENTATION OF CASE: The boy twisted his right knee and was seen at our facility 8 days later. Magnetic resonance imaging revealed an osteochondral fragment in the intercondylar fossa and a high-intensity area in the ACL midsubstance. This injury was diagnosed as a type III tibial eminence fracture by Meyers and McKeever classification. On the 10(th) day after the injury, the patient underwent arthroscopic reduction and fixation. During arthroscopy proximally displaced avulsion fragment in the intercondylar fossa was found. Although the continuity of the anteromedial bundle of the ACL was confirmed, the posterolateral bundle was completely torn and the tension of ACL was weakened. The fragment and torn ACL were fixed with pull out suture. One year after the operation, the patients can play sports without any pain. DISCUSSION: This case demonstrates that a tibial eminence fracture with an ACL midsubstance tear can occur in a child. Despite the rarity of such cases, preoperative MRI studies are necessary to detect and diagnose them. MRI also allows surgeons to identify cases that might need ACLR. CONCLUSION: It should be noted that a midsubstance ACL tear can occur with a tibial eminence fracture even in skeletally immature patients, and that preoperative MRI is necessary to diagnose and select the appropriate treatment.